Individuals with Autism Spectrum Disorder: A Review of Human Factors Considerations and Usability Testing Guidelines. (November 2019) - Tornblad, McKenna K.; Jones, Keith S.; Inan, Fethi A.
Individuals with autism spectrum disorder (ASD) display an interest in and affinity for technology; however this population's wide range of special needs is not often taken into account in technology design or usability testing. To assist human factors professionals in understanding this user population, we present a description of three domains of special needs for those with ASD: information processing, communication, and behavior. We then present a proposed model that human factors professionals could employ to understand the unique characteristics of individuals with ASD. We also synthesize research on design considerations for these users and present a composite list of recommendations for usability testing. Thus, this paper is intended to inform the human factors community of the unique characteristics of this user group, and provide guidelines for both design and usability testing.